Hubungan Literasi Digital Dan Efikasi Diri Dengan Kinerja Guru Sekolah Dasar Negeri Di Gugus 4 Dan Gugus 8 Kecamatan Bogor Barat Kota Bogor - Jalil, R Jefri Nurdin Abdul ; Ramdhani, Sendi; Maharani, Arry Rekno Ulta (Universitas Pakuan, 2025)
THE RELATIONSHIP BETWEEN DIGITAL LITERACY AND SELF-EFFICACY WITH THE PERFORMANCE OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN CLUSTER 4 AND CLUSTER 8, WEST BOGOR DISTRICT, BOGOR CITYThe ideal teacher performance is that a teacher can carry out his roles and duties as well as possible so as to produce quality graduates. This study, conducted at a State Elementary School located in clusters 4 and 8 of West Bogor District, Bogor City, with a population of 133 people and a sample of 100 respondents, aims to determine the relationship between digital literacy and self-efficacy on teacher performance. This study uses a robust quantitative research method, enhancing the reliability and validity of the findings. The independent variables are digital literacy and self-efficacy. While the dependent variable is teacher performance. The technique of collecting independent variable data is through a questionnaire distributed through a G-form, while the collection of dependent variable data is through teacher performance assessment. The results of the study The digital literacy variable was significantly related to the teacher performance variable, with a significance value of 0.000 which was smaller than 0.05. A correlation value of 0.467 indicates a positive relationship with a moderate level of relationship. The self-efficacy variable was significantly related to the teacher performance variable, with a significance value of 0.000 which was less than 0.05. A correlation value of 0.588 indicates a positive relationship with a moderate level of relationship. The multiple correlation test was known to have a Sig. F Change value of 0.000 0.05, it can be concluded that digital literacy and self-efficacy are jointly correlated with teacher performance. A correlation value of 0.629 indicates a positive relationship with a strong relationship level. So, digital literacy and self-efficacy are positively related to the performance of teachers who play an important role in the world of education.